NATURAL ZEOLITE FROM CIKANCRA, TASIKMALAYA: AMMONIUM ION STORE MEDIA FOR AMMONIUM SULPHATE FERTILIZER - Estiaty, Lenny Marilyn; Fatimah, Dewi; Yunaeni, Irma (Jurnal Zeolit Indonesia, 2004)
Nitrogen fertilizer is one of the fertilizer type which is required for plant growth. This fertilizer is easily dissolved and the ions are not clay bonded, that it is often washed out by rain, evaporated or changed to other forms which can not be used by plants. In order to increase the efficiency of N-fertilizer, the loss of N must be minimized. In other hand, it is well known that natural zeolites have the capability as adsorbents and cation exchangers, such as for ammonium ion. Investigation has been carried out to analyze the capability of natural zeolite from Cikancra, Tasikmalaya to store ammonium ion from ammonium sulfate fertilizer. This research can be used to predict the quantity of zeolite to be added to the soil if we use ammonium sulfate fertilizer. The natural zeolite applied has been selected of the highest cation exchange capacity (CEC) value zeolite from various particle sizes and activation method. The highest CEC, of 150.92 meq/100g is gained by activation at 105oC of particle size â20 +48 mesh. The optimum CEC of natural zeolite against ammonium sulfate fertilizer is 146.11 meq/100g in 0.2 N (NH4)2SO4 solution. Therefore, the quantity of ammonium sulfate fertilizer (ZA), which can be stored in 100g zeolite is 19.306 g.